Efectos del programa Fonojuego en los niveles de conciencia fonológica en niños de cinco años de la I.E.I. 102 - Ventanilla - Espinoza Rivera, Marlene Ricardina (2010)
The purpose of this investigation was to determine the effectiveness of “Fonojuego Program” in the phonological awareness level in five years old children`s group of the Elementary Educational Institute Nº 102 of Ventanilla – Callao. A group of 40 was selected children. After this, the children were chosen to conform the experimental and control group. The instrument used to obtain the data was “The Methalinguistic Abilities Test”. This test was developed by Gomez, Valero, Buades and Pérez, adapted by Panca (2003). This test applied to itself to the group control and experimentally, being the experimental group subject to the program Fonojuegos. The results were analyzed, statistically by means the Test U of Mann - Withney. Thinking that the application of the program Fonojuegos shows his efficiency on having increased significantly the levels of phonological conscience in all his evaluated components. Likewise one concludes the importance of developing the phonological conscience from early ages with the purpose of anticipating future problems of learnings related to the reading.